The Influence of Capital, Labor, Digital Payment, and E-Commerce on the Income of Food and Beverage SMEs in Denpasar City - Kadek Yuni Ariningsih; Surya Dewi Rustariyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Small and Medium Industries (SMEs) have become a crucial pillar of Indonesia's economy and have proven to be key drivers of economic resilience during times of crisis. According to data from the Department of Industry and Trade of Bali Province, the food and beverage SMEs in Denpasar City have the highest number of business units, totaling 1,002 units. However, the declining consumer interest in food and beverage SMEs has led to a decrease in their income. Capital, labor, the use of digital payment systems, and the adoption of e-commerce are expected to increase the income of food and beverage SMEs in Denpasar City. This study is a quantitative research involving a population of 1,002 food and beverage SME units. It aims to examine the effect of capital, labor, the use of digital payments, and e-commerce on the income of food and beverage SME actors in Denpasar City. The sample consists of 91 business units selected using a non-probability sampling method with a purposive sampling technique. The data were analyzed using multiple linear regression analysis. The findings indicate that capital, labor, the use of digital payment systems, and e-commerce have a simultaneous and significant effect on the income of food and beverage SME actors in Denpasar City. Furthermore, each variable capital, labor, digital payment usage, and e-commerce individually has a positive effect on income. The implication of this research is that increasing capital, adding labor, and promoting the use of digital payment systems and e-commerce can enhance the income of food and beverage SMEs in Denpasar City.